The sigma-1 receptor as a neurohomeostatic decision hub for GABARAP-mediated receptor trafficking and macroautophagy - Baeken, Marius Wilhelm; Bekbulat, Fazilet; Körschgen, Hagen; Clement, Albrecht Martin; Behl, Christian (Frontiers in Molecular Biosciences, 2025)
Gamma-aminobutyric acid receptor-associated protein (GABARAP) is a multifunctional member of the autophagy-related (ATG8) protein family, playing key roles in two distinct cellular pathways: macroautophagy and plasma membrane protein trafficking. In the context of autophagy, GABARAP modulates cargo recognition and supports the maturation and fusion of autophagosomes with lysosomes, a critical step in intracellular clearance and proteostasis. Separately, GABARAP also regulates vesicular receptor protein transport from the Golgi apparatus to the plasma membrane, contributing to proper surface localization and receptor recycling. Both tasks are especially vital for neurons, where protein turnover and receptor localization are tightly linked to synaptic plasticity and neuroprotection. We recently identified a direct interaction between GABARAP and the sigma-1 receptor (σ1R), an ER-resident receptor involved in diverse cellular stress responses, mitochondrial function, and protein homeostasis. Our findings suggest that σ1R acts as an upstream regulatory hub, influencing GABARAP’s functional commitment to either membrane trafficking or autophagy. Specifically, we hypothesize that ligand-dependent σ1R activation promotes GABARAP’s involvement in macroautophagy at the expense of its role in membrane transport. This regulatory switch may underline part of the neuroprotective effects observed with σ1R agonists in neurodegenerative disease models, where enhanced autophagy is often beneficial. Overall, we discuss the emerging molecular crosstalk between σ1R and GABARAP, its potential impact on neuronal homeostasis, and how σ1R’s pharmacological modulation might be leveraged to bias GABARAP function toward autophagy in diseases such as amyotrophic lateral sclerosis, Huntington’s, Parkinson’s, and Alzheimer’s disease.